The Effect of School-Based Quality Improvement Management and Achievement Motivation on Teacher Performance - Firman Edi; Sudadio Sudadio; Nurul Anriani (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The objective of this study is to examine the direct impact of school-based quality improvement management on teacher achievement motivation and performance, as well as the indirect impact of school-based quality improvement management on teacher performance through achievement motivation. The research population was 485 while the research sample was 220 public elementary school teachers in Tangerang Regency who were selected through random sampling. This research is quantitative research with path analysis to see the direct and indirect influence between research variables. The research data collection technique uses a questionnaire whose validity and reliability have been tested. From the data analysis, the research results showed that: Management-based quality improvement has a direct effect on teacher achievement motivation; School-based quality improvement management has a direct effect on teacher performance; School-based quality improvement management has an indirect effect on teacher performance through achievement motivation in Tangerang Regency State Elementary Schools. This means that achievement motivation can mediate the influence of school-based quality improvement management on teacher performance; Teacher achievement motivation has a direct influence on teacher performance in Tangerang Regency Public Elementary Schools. The implications of this research are to encourage greater autonomy in schools and improve overall school quality, which includes increasing teacher effectiveness and developing effective school leadership.